2021
DOI: 10.3926/jotse.1081
|View full text |Cite
|
Sign up to set email alerts
|

Why students use social networks for education: Extension of UTAUT2

Abstract: Social networks sites have a considerable impact on all our life aspects, especially the educational sector. This study aims at identifying the factors affecting students’ actual usage of social networks sites for educational purposes in Jordanian universities.  The proposed model consists factors of UTAUT2 theory (Effort expectancy, Performance expectancy, Social influence, Facilitating condition, Habit, Hedonic motivation). In addition to two added factors (lecturer support, and student-related factors) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
(46 reference statements)
6
16
4
Order By: Relevance
“…The findings of this study were however inconsistent with those of Huang and Kao (2015), Nguyen et al. (2014) and Abu-Garrah and Aljaafreh (2021), which found that habit significantly influenced the behavioural intentions of users to accept a system. With regards to price value, the findings of the current study are also inconsistent with studies of Moorthy et al.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The findings of this study were however inconsistent with those of Huang and Kao (2015), Nguyen et al. (2014) and Abu-Garrah and Aljaafreh (2021), which found that habit significantly influenced the behavioural intentions of users to accept a system. With regards to price value, the findings of the current study are also inconsistent with studies of Moorthy et al.…”
Section: Discussioncontrasting
confidence: 99%
“…, 2012). This was also confirmed in a study by Abu-Gharrah and Aljaafreh (2021), which established that effort expectancy significantly influenced the behavioural intentions of users to accept a system such as blended learning in universities.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations